Otohematoma in Cats - Cariola Viana, Paula; Lucas Castro de Oliveira, André; Ferreira, Arthur; Santos Guiotti, Izabelle; Denipoti de Oliveira, Sofia; da Silva Marques, Ana Beatriz; Merlini, Natalie Bertelis (Acta Scientiae Veterinariae, 2025)
Background: Otohematoma is a condition commonly encountered in the routine veterinary treatment of dogs and cats, characterized by trauma-derived damage to blood vessels and/or ear cartilage, leading to the accumulation of blood between the pinna cartilage and skin. Although the primary causes of this condition are not well defined, it is highly prevalent in animals with otitis externa, due to head movements and pruritus. In cats, otohematoma is typically associated with infestation by mites, particularly Otodectes cynotis. In this study, we report 2 cases of unilateral otohematoma in felines associated with parasitic otitis externa. Cases: Case 1. A 6-year-old indoor-outdoor male cat of no defined breed, weighing 4.5 kg. Vaccination, deworming, and ectoparasite control had not been updated, and the cat had not been tested for feline immunodeficiency virus (FIV) or feline leukemia virus (FELV). The owner’s main complaint was bilateral pruritus and an enhanced volume of the right ear pinna. Case 2. A 10-year-old spayed indoor-outdoor female cat of no defined breed, weighing 3.30 kg. Vaccination, deworming, and ectoparasite control had not been updated, and the cat had not been tested for FIV/FELV. The owner’s main complaint was pruritus, an increased volume in the animal’s right ear, and the presence of an ulcerative lesion in both ears. In both cases, general clinical examinations revealed no abnormalities. Blood tests were performed to determine blood counts. An otological inspection identified the presence of blackened dirt, a positive otopodal reflex upon handling, and lesions on the dorsal portion of the ear, with soft swelling throughout the right ear pinna. Both cats were diagnosed with bilateral otitis externa caused by O. cynotis, and were treated with selamectin [Revolution 6%® spot on, 45 mg, topically administered, single dose], regular ear cleaning, and referred for surgical correction of the otohematoma. Post-surgical care included meloxicam [Flamavet®, 0.05 mg/kg, orally administered, every 24 h for 4 days] and dipyrone monohydrate [Aberalgina®, 25 mg/kg, orally administered, every 24 h for 4 days]. In addition, the cats were fitted with an Elizabethan collar. Fifteen days post-surgery, the sutures were removed. The animals responded well to the treatment, with resolution of the abnormalities after surgery. Discussion: Otohematoma is considered a highly prevalent clinical condition in small animals, characterized by the accumulation of blood on the concave side of the ear, due to regional trauma of the auricular cartilage, with blood accumulating between the skin and cartilage. Otohematoma, which can be either partial or total, tends to be attributable to a primary cause, the most commonly described being otitis externa, and is generally more common in dogs than in cats, with prevalence rates of 5% - 20% and 2% - 6%, respectively. Among parasite-associated cases, the mite O. cynotis is the main causal agent of otitis externa in pets. An effective resolution of otohematoma requires the identification and resolution of the primary cause. In the cases described herein, conservative treatment with drainage and compressive bandaging was not possible due to the upright shape of the cats’ ears and difficulty in using an Elizabethan collar. Consequently, surgical correction was selected for treatment, which generally provides good resolution and has low rates of recurrence. Keywords: aural hematoma, otitis externa, Otodectes cynotis. Título: Otohematoma em gatos Descritores: hematoma aural, otite externa, Otodects cynotes.